Lignocellulosic fibre and biomass-based composite materials processing, properties and applications - Jawaid, Mohammad; Tahir, Paridah Md; Saba, Naheed (Woodhead Publishing series in composites science and engineering, 2017)
Lignocellulosic Fibre and Biomass-Based Composite Materials reviews the development, characterization and applications of composite materials developed from the effective use of lignocellulosic fibre and biomass. The book gathers together a wide spectrum of cutting-edge research on biomass fillers and reinforcements used for the fabrication and synthesis of composites. The book takes a systematic approach, investigating processing, design, characterization and applications of biocomposites, in order to establish their important relationship as a general guideline for end-user applications. Beginning with an introduction to biomass and its composites, a team of leading experts in the field cover rice husk, kenaf, oil palm, alfa and doum fibres, bamboo, cork, and many other materials, considering a range of applications, along with key issues such as performance and sustainability. The groundbreaking research presented opens the door to obtaining advanced material characteristics and significant enhancements in physical, mechanical, and thermal properties. This will be become an extremely useful reference and technical guide for academic and industrial researchers in composite materials, as well as for advanced students and industrialists working in material commercialization.--Provided by publisher.